Diversity and Selection of Superior Algarrobos (Neltuma pallida) Phenotypes in the Natural Dry Forests of Peru for Sustainable Conservation and Genetic Improvement - Casas Niño, Sebastian (2025)
Neltuma pallida (algarrobo) is a keystone species of the Peruvian dry forest whose persistence is threatened by overexploitation and habitat degradation, making its conservation and genetic improvement a national priority. This study aimed to identify outstanding phenotypes of N. pallida through phenotypic characterization in the regions of Piura and Tumbes in northern Peru. A stratified random sampling design was applied, establishing forest plots in 13 localities and evaluating 631 adult individuals. Dendrometric and phenotypic traits were recorded together with physiographic, climatic, and edaphic variables obtained from soil analyses and geographic information systems. Phenotypic differentiation among populations was assessed using the index PST, which quantifies between- and within-population variance components. High morphological variability was detected across populations, with significant differences in tree height, diameter, and fruit production, largely explained by environmental heterogeneity, particularly soil fertility and organic matter. The PST values, ranging from 0.83 to 0.98, revealed strong phenotypic divergence among populations, suggesting adaptive differentiation rather than neutral variation. Eight superior individuals were identified as potential candidates for inclusion in a germplasm bank to support breeding and restoration programs. This study provides a scientific basis for the sustainable management and conservation of N. pallida in the arid ecosystems.